(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This note reports the faunal species associated with mangroves and other wetlands in nocturnal periods in the Vía Parque Isla de Salamanca in order to support management and conservation planning for this natural park. The study was carried out from September through December 2006 using nocturnal surveys. We report 19 species including invertebrates such as arachnids, crustaceans, and mollusks, and vertebrates such as amphibians, reptiles, birds, and mammals. We focused on those species that are classified as threatened either nationally or internationally, and those for which VIPIS represents an information need and an important area for ensuring their persistence.